Mozart and Leadbelly stories and essays - Gaines, Ernest J. 1933-2019 (Knopf, 2005)
Collects five stories, set in Louisiana, that capture the joys and sorrows of rural Southern life, accompanied by prose works that chronicle the author's life as a writer, and the people and places that he has encountered.
Keywords: Gaines, Ernest J -- 1933- -- Childhood and youth; Gaines, Ernest J. -- 1933-2019; Geschichte 1900-2000; Alltag, Brauchtum; Schwarze. USA; Authors, American -- 20th century -- Biography; African American authors -- Biography; African Americans -- Fiction; Literatur; Schwarze; Louisiana -- Social life and customs -- Fiction; California -- Biography; Louisiana -- Biography; Louisiana; Autobiografie